Pengaruh Bauran Pemasaran Jasa Terhadap Loyalitas Nasabah Pada PT Bank SulSel-Bar Cabang Utama Makassar - Mansyur, Mansyur; Khatimah, Khusnul; Indrayani, Syarthini (Universitas Negeri Surabaya, 2024)
This study aims 1) to find out how to determine customer loyalty at PT bank Sulsel-bar Makassar main branch through the service marketing mix. The type of research used in this research is quantitative with a sample of 84 respondents. Data collection techniques using questionnaire techniques. The data analysis technique uses the classic assumption test. The results showed 1) Products have a positive and significant effect on customer loyalty at PT. Bank Sulsel-Bar Makassar Main Branch means that the better the product at PT bank Sulsel bar Makassar main branch, the customer loyalty will increase. 2) Price has a positive and significant effect on customer loyalty at PT. Bank Sulsel-Bar Makassar Main Branch the better the price at PT Bank Sulsel-bar Makassar main branch, the customer loyalty is increasing. 3) Promotion has a positive and significant effect on customer loyalty at PT. Bank Sulsel-Bar Makassar Main Branch the better the promotion at PT Bank Sulsel-bar Makassar main branch, the customer loyalty increases. 4) Place has a positive and significant effect on customer loyalty at PT. Bank Sulsel-Bar Makassar Main Branch the better the place at PT Bank Sulsel-bar Makassar main branch the customer loyalty also increases 5) People have a positive and significant effect on customer loyalty at PT. Bank Sulsel-Bar Makassar Main Branch the better the people at PT Bank Sulselbar Makassar Main branch the customer loyalty also increases 6) The Physical Environment has a positive and significant effect on customer loyalty at PT. Bank Sulsel-Bar Makassar Main Branch means that the better the physical environment at PT Bank Sulsel-bar Makassar main branch, the customer loyalty also increases 7) The process has a positive and significant effect on customer loyalty at PT. Bank Sulsel-Bar Makassar Main Branch means that the better the process at PT Bank Sulsel-bar Makassar main branch, the customer loyalty will also increase.